Exploring the Moderating Role of Gender in the Relationship between Personality Traits and Entrepreneurial Competencies - Cabusao, Marinela B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study examines the interplay between personality traits, gender, and entrepreneurial tendencies. Drawing from the framework of the Big Five personality traits (Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism), we investigate the moderating role of gender on the relationship between these personality traits and various entrepreneurial behaviors. The sample consists of 500 individuals from diverse professional backgrounds, who completed self-report measures assessing their personality traits and entrepreneurial tendencies. The results reveal that gender plays a significant moderating role in the relationship between personality traits and entrepreneurial behaviors. Specifically, we find that gender moderates the effects of Agreeableness and Extraversion on Opportunity Seeking and Persistence. Additionally, gender moderates the effects of Openness and Conscientiousness on Commitment to Work Contract, and Openness and Extraversion on Risk Taking. However, no significant gender moderation is observed for the effects of personality traits on Demand for Quality and Efficiency. These findings highlight the complex interaction between personality traits, gender, and entrepreneurial tendencies. Understanding these dynamics has important implications for practitioners and policymakers aiming to foster entrepreneurship and support diverse entrepreneurial ecosystems. By acknowledging the differential impact of personality traits on entrepreneurial behaviors based on gender, tailored interventions and training programs can be developed to empower individuals, irrespective of their gender, in their pursuit of entrepreneurial success. Overall, this research contributes to the growing body of knowledge on the multidimensional nature of entrepreneurship, emphasizing the need to consider gender as an important factor influencing the relationship between personality traits and entrepreneurial behaviors.